Evaluation of knowledge, attitudes and vaccine hesitancy towards MMR vaccine among parents in the United Arab Emirates - Kamel A. Samara; Hiba Jawdat Barqawi; Deema M. Alhayali; Samah Mohamed Kannas; Rim M. Elmorsy; Eman Abu-Gharbieh (PLoS ONE, 2025)
Background The Measles, Mumps, and Rubella (MMR) vaccine is highly effective, but vaccine hesitancy (VH) is a key barrier to achieving herd immunity. This study aims to assess the general attitudes and knowledge of UAE parents regarding measles and the MMR vaccine while identifying determinants of VH. Methodology A cross-sectional study was done from 15th April 2024 and 5th June 2024. This study recruited 462 parents residing in the UAE using convenience sampling. Recruitment occurred through various social media platforms including WhatsApp, X, and Instagram, as well as in public by approaching parents in parks and malls. Information collected included demographic factors, measles knowledge, MMR attitudes and practices as well general vaccine attitudes using the Parental Attitudes toward Childhood Vaccines (PACV) and the WHO Vaccine Hesitancy Scale (VHS). Univariate, bivariate (chi-squared tests) and multivariate (logistic regression) analyses were conducted to identify significant factors contributing to vaccine hesitancy. Results Of 462 participants, 87% were female, 41% were young adults, and 13.0% were healthcare workers. 15.6% of parents had no knowledge about measles and 20.0% had not heard of the MMR vaccine before. Healthcare professionals and specialist doctors were the most trusted sources of information regarding measles. Symptoms and transmission were generally well-recognized but there was a lack of knowledge regarding measles’ severity, epidemiology, and complications. 11.5% of parents believed the MMR vaccine can cause autism and 21.65% of parents (95% CI: 18.1–25.6%) were vaccine hesitant. Intention to vaccinate against measles was the strongest predictor of reduced vaccine hesitancy (AOR: 0.242, 95% CI: 0.143–0.410), followed by being middle-aged/older (AOR: 0.466, 95% CI: 0.281–0.772) and interest in learning more about measles (AOR: 0.394, 95% CI: 0.185–0.840). Conclusions In the UAE, there are knowledge gaps regarding measles and concerns regarding the Measles, Mumps, and Rubella vaccine’s safety and efficacy. Parents who refuse MMR vaccination often demonstrate general vaccine hesitancy, necessitating prompt action to reestablish trust in the local vaccine programs and promote vaccination.